Students’ sociocultural perspectives in online EFL learning in Indonesia - Dodi Erwin Prasetyo (Universitas Merdeka Malang, 2025)
Research examining sociocultural perspectives in online EFL learning within the Indonesian context remains limited. This study aimed to explore students’ sociocultural perspectives in digitally mediated EFL learning and to examine whether sociocultural interaction patterns differed across gender. Using a descriptive quantitative design, the study involved 27 senior high school students in East Java, comprising 21 females and 6 males. Data were collected through a questionnaire adapted from established sociocultural indicators—social act, distributed context, invention perspective, dialogism, and intertextuality—and analyzed using descriptive statistics and the Mann–Whitney U test. The findings indicate that most students demonstrated positive sociocultural engagement in online learning, including understanding instructional explanations, seeking help, using additional learning resources, and participating in discussions with teachers and peers. The analysis further revealed no statistically significant differences between male and female students across all sociocultural indicators. These findings suggest that sociocultural interaction in online EFL learning is shaped more by mediated learning environments than by gender differences, offering pedagogical implications for designing interactive and supportive online EFL instruction.